Algoriphagus pacificus sp. nov. and Algoriphagus oliviformis sp. nov., isolated from a mariculture fishpond. Issue 7 (22nd July 2021) - Lu, Huibin; Cai, Zhipeng; Deng, Tongchu; Qian, Youfeng; Xu, Meiying
Abstract : Two Gram-stain-negative, catalase-positive, oxidase-negative, rod-shaped, non-flagellated, non-spore-forming and non-motile strains (YJ13C T and H41 T ) were isolated from a mariculture fishpond in PR China. Comparisons based on 16S rRNA gene sequences indicated that YJ13C T and H41 T shared 16S rRNA gene sequences similarities between 92.6 and 99.2 % with species of the genus Algoriphagus . YJ13C T only shared 93.8 % 16S rRNA gene sequence similarity with H41 T . The reconstructed phylogenetic and phylogenomic trees indicated that YJ13C T and H41 T clustered closely with species of the genus Algoriphagus . The calculated pairwise orthologous average nucleotide identity with usearch (OrthoANIu) values between strains YJ13C T and H41 T and other related strains were all less than 79.5 %. The OrthoANIu value between YJ13C T and H41 T was only 69.9 %. MK-7 was the predominant respiratory quinone of YJ13C T and H41 T and their major cellular fatty acids contained iso-C15 : 0, C16 : 1 ω7 c and C17 : 1 ω9 c . The polar lipids profiles of YJ13C T and H41 T consisted of phosphatidylethanolamine and several kinds of unidentified lipids. Combining the above descriptions, strains YJ13C T and H41 T represent two distinct novel species of the genus Algoriphagus, for which the names Algoriphagus pacificus sp. nov. (type strain YJ13C T =GDMCC 1.2178 T =KCTC 82450 T ) and Algoriphagus oliviformis sp. nov. (type strain H41 T =GDMCC 1.2179 T =KCTC 82451 T ) are proposed.